Transcranial Doppler in 150 Congolese children with sickle cell disease - Kazadi, Gisele Tshiama; Mbuyi, Didier Mukendi; Kitenge, Robert; Mpaka, Smith; Gini, Jean Lambert Ehungu; Ngiyulu, René; Tshilolo, Léon Muepu (Frontiers in Stroke, 2024)
Introduction: Sickle Cell Disease (SCD) ranks among the most prevalent genetic disorders globally. The incidence in sub-Saharan African countries has been estimated to be 230.000/y with a high prevalence (1%) in the Democratic Republic of Congo (DRC). Stroke is a significant complication of Sickle Cell Disease (SCD), and carries a high risk of disability and mortality. Transcranial Doppler (TCD) is currently the non-invasive exploration recommended for the prevention of stroke in young SCD patients. Objective: To determine the prevalence of pathological TCD in a population of young Congolese SCA patients and to assess its association with hematological parameters. Population and Methods: This cross sectional study was carried out on 150 Congolese SS homozygous children between the ages 2-16 years old (mean age: 8.5±4.0 years) in stable condition, and followed from January 1 to December 31, 2013. TCD was performed using the STOP I method in the main cerebral arteries. The risk of stroke was absent when the average maximum speed during a cycle (TAMMV) in middle cerebral artery (MCA) was < 170cm/sec, but present when TAMMV was borderline or conditional for values between 170-199 cm/sec and pathological for values ≥ 200 cm /sec. Results: The prevalence of pathological TCD was 4% while the conditional TCD prevalence was 10%. The Mean blood velocity in MCA was 114.0 cm/sec. There was a significant difference in the means of WBC (p = 0.003), Hb (p < 0.001), Hct (p < 0.001), MCV (p = 0.005) parameters when comparing normal and at risk TCD (conditional and abnormal). However, no significant association was found for the categorical corresponding parameters Conclusion: Globally, 14% of patients were at risk of stroke, hence the interest in integrating TCD in the routine monitoring of children with SCD in order to prevent overt stroke by implementing a chronic blood transfusion program or the use of hydroxycarbamide. Keywords: Sickle Cell Disease, Democratic Republic of Congo, Abnormal Transcranial Doppler, Hydroxyurea, Fetal haemoglobin, Stroke.